2004
DOI: 10.1136/bmj.329.7471.895
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments: Suicide in older people

Abstract: There is but one truly serious philosophical problem, and that is suicide Albert CamusElderly people have a higher risk of completed suicide than any other age group worldwide. 1 Despite this, suicide in elderly people receives relatively little attention, with public health measures, medical research, and media attention focusing on younger age groups.2 We outline the epidemiology and causal factors associated with suicidal behaviour in elderly people and summarise the current measures for prevention and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
0
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(190 citation statements)
references
References 20 publications
(25 reference statements)
7
170
0
13
Order By: Relevance
“…Earlier research showed that older people tend to commit complete suicide among general population 19, 20. Older patients with cancer are also high‐risk group, which is consistent with our research 21, 22, 23.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Earlier research showed that older people tend to commit complete suicide among general population 19, 20. Older patients with cancer are also high‐risk group, which is consistent with our research 21, 22, 23.…”
Section: Discussionsupporting
confidence: 92%
“…Older patients usually encountered with greater disease burden, and social psychological pressure. Higher suicide rate of older NSCLC patients may be related to pressure and depression 20. Another possible reason is that, they hold the rational will of ending their life at the right time 24.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, for depressed individuals, negative cognitions associated with hopelessness and low self-esteem may lead to thoughts of death or thoughts that life is not worth living and death ideation. This negative thinking style may then progress to suicidal ideation (Heisel & Flett, 2005;O'Connell, Chin, Cunningham, & Lawlor, 2004). Several studies have offered some preliminary support of our model.…”
Section: Depression and Negative Cognitive Biasmentioning
confidence: 86%
“…Worldwide demographic aging means that the absolute number of suicides by older people is likely to increase (O'Connell et al 2004;Yur'yev et al 2010). The results of this study showed that there was large difference in magnitude of the suicide rate ratios between the older (65?)…”
Section: Discussionmentioning
confidence: 99%